WHEN SHIFTS MEET LIFE: Balancing Production Demands and Employee Well-Being in Indonesian Manufacturing - Munawaroh Munawaroh; Aan Destian; Dira Rizki Amalia; Asep Chandra; Putriana Putriana (Yayasan Education and Social Center, 2026)
Work-life balance and employee well-being represent critical imperatives in contemporary manufacturing human resource management, where intensive production demands and shift-based systems create inherent tensions between organizational productivity and worker welfare. This qualitative case study examines the implementation of work-life balance and its multidimensional impact on employee well-being at PT Knauf Plasterboard Indonesia Cilegon Plant a representative Indonesian manufacturing facility operating under high-pressure production conditions, through in-depth interviews with 15 purposively-selected employees (encompassing operational shift workers, administrative non-shift personnel, and HR management), direct workplace observations, and systematic document analysis, this research reveals nuanced dynamics between organizational policies and lived employee experiences. Findings demonstrate that while structured working hours, rotation shift systems, and welfare facilities provide foundational support for work-life balance, persistent high production targets pose significant challenges that undermine its effectiveness. The study establishes that enhanced work-life balance correlates positively with the physical, psychological, and social well-being dimensions, though variations in work intensity moderate these relationships. Research contributions include empirical evidence from underexplored Indonesian manufacturing contexts and actionable recommendations for reconciling productivity imperatives with sustainable employee well-being practices.